Combining daratumumab with CD47 blockade prolongs survival in preclinical models of pediatric T-ALL - Müller, Kristina; Vogiatzi, Fotini; Winterberg, Dorothee; Rösner, Thies; Lenk, Lennart; Bastian, Lorenz; Gehlert, Carina L.; Autenrieb, Marie-Pauline; Brüggemann, Monika; Cario, Gunnar; Schrappe, Martin; Kulozik, Andreas; et al. (Blood, 2022)
Acute lymphoblastic leukemia (ALL) is the most common malignant disease affecting children. Although therapeutic strategies have improved, T-cell acute lymphoblastic leukemia (T-ALL) relapse is associated with chemoresistance and a poor prognosis. One strategy to overcome this obstacle is the application of monoclonal antibodies. Here, we show that leukemic cells from patients with T-ALL express surface CD38 and CD47, both attractive targets for antibody therapy. We therefore investigated the commercially available CD38 antibody daratumumab (Dara) in combination with a proprietary modified CD47 antibody (Hu5F9-IgG2σ) in vitro and in vivo. Compared with single treatments, this combination significantly increased in vitro antibody-dependent cellular phagocytosis in T-ALL cell lines as well as in random de novo and relapsed/refractory T-ALL patient-derived xenograft (PDX) samples. Similarly, enhanced antibody-dependent cellular phagocytosis was observed when combining Dara with pharmacologic inhibition of CD47 interactions using a glutaminyl cyclase inhibitor. Phase 2-like preclinical in vivo trials using T-ALL PDX samples in experimental minimal residual disease-like (MRD-like) and overt leukemia models revealed a high antileukemic efficacy of CD47 blockade alone. However, T-ALL xenograft mice subjected to chemotherapy first (postchemotherapy MRD) and subsequently cotreated with Dara and Hu5F9-IgG2σ displayed significantly reduced bone marrow infiltration compared with single treatments. In relapsed and highly refractory T-ALL PDX combined treatment with Dara and Hu5F9-IgG2σ was required to substantially prolong survival compared with single treatments. These findings suggest that combining CD47 blockade with Dara is a promising therapy for T-ALL, especially for relapsed/refractory disease harboring a dismal prognosis in patients.
Gesehen am 25.09.2022